Pengaruh Model Discovery Learning Terhadap Pemahaman Konsep Siswa SMA Berbantuan Software Tracker pada Materi GHS - Maya Aprilia; Patricia Hotma Minar Lubis; Linda Lia (Department of Physics Education, Universitas Mataram, 2020)
This study aims to analyze the effect of the Discovery Learning model on the conceptual understanding of high school students assisted by tracker software on simple harmonic vibration (GHS) material. The method used in this research is quantitative research with a Quasi Experiment design type Posttest Only Control Design. The population in this study were all class X SMA Pembina Palembang which consisted of 2 classes. The sampling technique used saturated sampling because all members of the population were sampled in this study. Class X IPA 1 as an experimental class applied Discovery Learning model assisted by tracker software and class X IPA 2 as a control class applied Discovery Learning model. The data collection technique used a concept understanding essay test instrument as many as 10 questions. The results showed that the mean understanding of the concept of the experimental class students was average = 84.90 and the control class was average= 74.08. The results of the right-side hypothesis test are tcount Ã¢â°Â¥ ttable, which is 7,567 Ã¢â°Â¥ 1,653. This means that Ha is accepted. Then the conclusion is that physics learning by applying the Discovery Learning model assisted by tracker software on simple harmonic vibration (GHS) material has an influence on the conceptual understanding of high school students rather than using a learning model without being balanced with learning media.